ADAPTATION AND CONSERVATION OF THE FINE ARTS MUSEUM IN THE KASATRIYAN COMPLEX AT THE KERATON OF YOGYAKARTA - Arthur Pramudya (Riset Arsitektur (RISA), 2017)
Abstract- At present, the Fine Arts Museum at the Keraton of Yogyakarta is still intact, though it has seen slight change and is less than comfortably equipped for certain activities. This research study aims to reveal the cultural significance of the objects and the architectural elements that have shaped them, followed by a description of preservation measures. The research method is qualitative-interpretative, along with the Architectural Approach (function-form-meaning), Architectural Typology, and the Conservational Approach. The cultural significance of the formal aspects falls under architectural values and skills, whereas the functional aspect takes on the form of purpose-based values and history-related values.The building with its massive shape has been adapted to its environment or immediate surroundings, in addition to having been ornamented. The spatial arrangement shows a symmetrical pattern. The thick walls protect it against the local tropical climate. The function of the building has changed drastically, namely from being a school to a residence for the Crown Prince, to its final transformation into a museum. The ornaments on the ceiling, railings, walls, gable and columns reveal a decidedly mixed style consisting of Art Nouveau, the typical Indies style, and local Javanese architecture. The skill-related values reveal the technology behind the shaping elements of the structural and architectural construction. The current purpose-based values refer to its present use as a Fine Arts Museum.The period spanning 1921-1934 forms the reference point for conservation. The condition of the building is still intact and solid, but there is some ambiguity in terms of temporal context (era) discernible, and there is minor damage, as well as less than satisfactory suitability for its current purpose. Conservation measures include adaptation of the building in accordance with its current function and preservation in the shape of routine maintenance.Keywords: Fine Arts Museum, cultural meaning, adaptation, conservation